Albendazole and Treatment of Hydatid Cyst: Review of the Literature - Dehkordi, Azar B.; Sanei, Behnam; Yousefi, Morteza; Sharafi, Seyedeh M.; Safarnezhad, Farhang; Jafari, Rasool; Darani, Hossein Y. (Infectious Disorders - Drug Targets, 2019)
Human hydatid cyst or cystic echinococcosis is a life-threatening zoonotic disease that occurs in most countries worldwide and is recognized as a major public health problem. Following ingestion of Echinococcus granulosus eggs, hydatid cysts which are the larval stage of the worm are formed mostly in liver and lungs, and occasionally in other organs of human. The usual treatment for hydatid cyst is open surgery. One of the problems following surgery is the recurrence. In the last decades, albendazole has been used for the treatment of hydatid cyst. This drug can be used alone or jointly with surgical procedures. However, its efficacy has not been well documented. Thus, in this work, the treatment of hydatid cyst with albendazole in different investigations including case studies, clinical trials in human and experimental works in animals has been reviewed. According to the findings of this review, it can be concluded that treatment of hydatid cyst with albendazole may be associated with the prevention of recurrence and reduction of the size and death of the hydatid cysts.
Keywords: cystic echinococcosis